(untitled) (Annual of the Faculty of Philosophy in Skopje, 2008)
In this work we give special emphasis to the developing period which caused disorder in the system of values and imposed two problems : on one hand, the problem caused by change of values in a society and on the other hand, how much we are prepared to accept those changes. The basic objective of this work is to focus its attention on the educational and upbringing process as one essential determinative change of the consciousness embracing the values for constitution democratic-civilian society, changes concerning the opening process in considering the qualities of citizen ’s life and personality. Democratic society promotes values of long duration just as: respect of the Declaration Human Rights, religious, ethnical, racial and cultural tolerance, pluralism, solidarity, collective responsibility,civilian coexistence, freedom, e.t.c. The adoption of the democratic principles and values of the civilian society are shown in the optimum of the individuals behaviour. Solving of the problems of discrimination, inequality, social marginalization, the authoritativeness of the social system and similar other problems, besides knowledge, requires active following of the changes, which is again connected to the moral belief based on the positivistic-utilitarian attitude towards the world. For several years the search for new moral principles of humans ’ life is stopped on the idea for global ethics. In this work I have presented results from a researsh mainly focused on the results from a survey conveyed on the young people ’s values and their life orientations in the period of development (1991-2004) that still lasts. The basic problem that Macedonian society faces today is how to fortify the strategies, the dynamics and the directions of the authentic development of the civilian values and attitudes throughout the education and the upbringing.